Mapping Global Research on Entrepreneurial Orientation - Judijanto, Loso (West Science Business and Management, 2025)
This study aims to map the intellectual structure and global evolution of research on Entrepreneurial Orientation (EO) using a bibliometric analysis approach. Drawing data from the Scopus database, a total of peer-reviewed journal articles were analyzed to uncover trends, influential authors, institutional collaborations, and thematic clusters in EO literature. Using VOSviewer software, co-authorship networks, keyword co-occurrences, and temporal visualizations were generated to provide insight into the development of the field. The results reveal that EO remains a core construct in entrepreneurship research, often linked with themes such as innovation, firm performance, strategic orientation, and small and medium-sized enterprises (SMEs). More recent trends indicate a shift toward sustainability, social entrepreneurship, and academic entrepreneurship, highlighting EO’s growing interdisciplinary appeal. The study contributes by consolidating fragmented knowledge, identifying emerging areas for inquiry, and offering a roadmap for future research and policy development. Despite its limitations, the findings provide valuable theoretical and practical guidance for scholars, educators, entrepreneurs, and policymakers navigating the evolving entrepreneurial landscape.
Keywords: Entrepreneurial Orientation; Bibliometric Analysis; Innovation; Firm Performance